The economic costs of extreme weather events: A hydro-meteorological CGE analysis for Malawi - Pauw, Karl; Thurlow, James; Bachu, Murthy; van Seventer, Dirk (Cambridge University Press, 2011)
Extreme weather events such as droughts and floods have potentially damaging implications for developing countries. Previous studies have estimated economic losses during hypothetical or single historical events, and have relied on historical production data rather than explicitly modeling climate. However, effective mitigation strategies require knowledge of the full distribution of weather events and their isolated effects on economic outcomes. We combine stochastic hydrometeorological crop-loss models with a regionalized computable general equilibrium model to estimate losses for the full distribution of possible weather events in Malawi. Results indicate that, based on repeated sampling from historical events, at least 1.7 per cent of Malawi's gross domestic product (GDP) is lost each year due to the combined effects of droughts and floods. Smaller-scale farmers in the southern region of the country are worst affected. However, poverty among urban and nonfarm households also increases due to national food shortages and higher domestic prices.